2019
DOI: 10.1007/978-3-662-58820-8_17
|View full text |Cite
|
Sign up to set email alerts
|

Verifiability of Helios Mixnet

Abstract: We study game-based definitions of individual and universal verifiability by Smyth, Frink & Clarkson. We prove that building voting systems from El Gamal coupled with proofs of correct key generation suffices for individual verifiability. We also prove that it suffices for an aspect of universal verifiability. Thereby eliminating the expense of individualverifiability proofs and simplifying universal-verifiability proofs for a class of encryption-based voting systems. We use the definitions of individual and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For instance, Smyth, Frink & Clarkson [34] have shown that neither Helios-C (an extension of Helios) [9] nor JCJ (an election scheme achieving coercion resistance) [16] satisfy the definition of universal verifiability, and propose a variant of JCJ that does. Moreover, Smyth has shown that implementations of the mixnet variant of Helios do not satisfy universal verifiability, and proposes a variant that satisfies both universal verifiability [32] and ballot secrecy [30].…”
Section: Closing Remarksmentioning
confidence: 99%
“…For instance, Smyth, Frink & Clarkson [34] have shown that neither Helios-C (an extension of Helios) [9] nor JCJ (an election scheme achieving coercion resistance) [16] satisfy the definition of universal verifiability, and propose a variant of JCJ that does. Moreover, Smyth has shown that implementations of the mixnet variant of Helios do not satisfy universal verifiability, and proposes a variant that satisfies both universal verifiability [32] and ballot secrecy [30].…”
Section: Closing Remarksmentioning
confidence: 99%
“… Smyth [38] shows that vulnerabilities in Helios cause vulnerabilities in implementations of the mixnet variant and proves verifiability is satisfied when a fix is applied.…”
mentioning
confidence: 92%
“…The definitions we have formally verified are inspired by Smyth et al [41]; specifically, we formally verify that the cryptographic verifier we generate guarantees both the correctness and soundness aspect of the universal verifiability of the scheme. This is the best that can be achieved for a scheme like Helios where castas-intended and collected-as-cast verifiability are not universally verifiable.…”
Section: Introductionmentioning
confidence: 99%